OpenElectrophy: an electrophysiological data- and analysis-sharing framework - Garcia, Samuel; Fourcaud-Trocmé, Nicolas (Frontiers in Neuroinformatics, 2009)
Progress in experimental tools and design is allowing the acquisition of increasingly large datasets. Storage, manipulation and efficient analyses of such large amounts of data is now a primary issue. We present OpenElectrophy, an electrophysiological data and analysis sharing framework developed to fill this niche. It stores all experiment data and meta-data in a single central MySQL database, and provides a graphic user interface to visualize and explore the data, and a library of functions for user analysis scripting in Python. It implements multiple spike sorting methods, and oscillation detection based on the ridge extraction methods due to Roux et. al., 2007. OpenElectrophy is open-source and is freely available for download at http://neuralensemble.org/trac/OpenElectrophy.